Moderating emotional intelligence and religiusity on the effect of burnout on turnover intentions of tax consultant employees in Bali - Astuti, Luh Citra Wirya; Dwirandra, A A N B; Astika, Ida Bagus Putra; Wirajaya, I Gde Ary (Linguistics and Culture Review, 2022)
The purpose of this study was to analyze the effect of burnout on the turnover intentions of tax consultant employees in Bali with emotional intelligence and religiosity as moderating variables. The location of the research was carried out at the Tax Consultant Office in the Bali Region as a representation of the Tax Consultant Office in Indonesia, which was registered with the Indonesian Tax Consultant Association (IKPI) in 2021 which was obtained through the website www.ikpi.or.id. The population in this study are all employees who work at the Tax Consultant Office registered at IKPI Bali Branch. The data analysis technique used the MRA test. The results of the study indicate that burnout has a positive and significant effect on turnover intention or in other words, increased burnout will increase turnover intention. The higher emotional intelligence is not able to reduce the high turnover intention due to the increased burnout of tax consultant employees. The interaction between burnout and emotional intelligence has a negative and significant effect on turnover intention or in other words, high emotional intelligence will reduce turnover intention due to increased burnout.